A Systematic Review of Self-directed Learning in Medical Education in Undergraduate Medical Students - Dharmendra Kumar Gupta; Arunima Chaudhuri; Dip Gaine (Current Medical Issues)
Self-directed learning (SDL), which emphasizes the need for students to take ownership of their learning, has become a crucial part of medical education. With the increasing complexity of health care, SDL is seen as a crucial skill for fostering lifelong learning and adapting to new challenges. This systematic review examines the current landscape of SDL in undergraduate medical education, exploring its effectiveness, implementation strategies, and areas for future development. A methodical exploration was carried out within the PubMed database to locate pertinent research articles released between 2012 and 2024. Studies that reported results pertaining to academic achievement, clinical competence, or student perspectives and that concentrated on SDL in undergraduate medical education were included. Two reviewers independently extracted the data, evaluated its quality, and synthesized the results thematically. In all, twenty-three papers were covered in this study. The findings indicate SDL positively impacts students’ academic performance and clinical skills, with many students reporting increased engagement and motivation. Effective implementation strategies included integrating SDL into the curriculum, providing faculty support, and utilizing digital tools to enhance learning. However, the review also identified significant heterogeneity in the definition and assessment of SDL across studies, as well as challenges related to student self-regulation and faculty preparedness. SDL is a useful method in medical education for undergraduates since it helps students become self-reflective, independent practitioners. To fully comprehend its long-term effects, however, longitudinal research, faculty development initiatives, and standardized SDL frameworks are required.